[Public Relations Strategies for Minnesota] - STUNTZ, SUSAN (Tufts Archival Research Center, 2007)
Copy; Confidential; Cover letter for public relations strategies to combat Minnesota State Plan for Nonsmoking and Health. Expresses that the Tobacco Institute (TI) has been 'overwhelmed' by events in Minnesota. Hopes that the attached strategies can be used in any state with similar issues.